A UV detector for microfluidic devices - Weldegebriel, Amos (Kansas State University, 2014)
Chemical separation involves selective movement of a component out of a region shared by multiple components into a region where it is the major occupant. The history of the field of chemical separations as a concept can be dated back to ancient times when people started improving the quality of life by separation of good materials from bad ones. Since then the field of chemical separation has become one of the most continually evolving branches of chemical science and encompasses numerous different techniques and principles. An analytical chemist’s quest for a better way of selective identification and quantification of a component by separating it from its mixture is the cause for these ever evolving techniques. As a result, today there are numerous varieties of analytical techniques for the separation of complex mixtures. High Performance Liquid Chromatography (HPLC), Gas Chromatography (GC), Capillary Electrophoresis (CE) and Gel Electrophoresis are a few out of a long list. Each these techniques manipulates the different physical and chemical properties of an analyte to achieve a useful separation and thus certain techniques will be suited for certain molecules. This work primarily focuses on the use of Capillary Electrophoresis as a separation technique. The mechanism of separation in Capillary Zone Electrophoresis and principles of UV detection will discussed in chapter one. Chapter two contains a discussion about the application of Capillary Electrophoresis (CE) on microfluidc devices. This will include sections on: microfabrication techniques of PDMS and photosensitized PDMS (photoPDMS), a UV detector for microfluidic devices and its application for the detection of wheat proteins. In Chapter three we report the experimental part of this project which includes; investigations on the effect of UV exposure time and thermal curing time on feature dimensions of photoPDMS microfluidic device, investigations on the injection and separation performances of the device, characterization of a UV detector set up and its application for the separation and detection of wheat gliadin proteins. The results of these investigations are presented in chapter four.
Keywords: UV detector for microfluidic devices; Microchip capillary electrophoresis; Gliadin wheat protein; Chemistry (0485)